Machine Learning and Robot Perception - Apolloni, Bruno; Ghosh, Ashish; Alpaslan, Ferda; Patnaik, Srikanta; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
This book presents some of the most recent research results in the area of machine learning and robot perception. The chapters represent new ways of solving real-world problems. The book covers topics such as intelligent object detection, foveated vision systems, online learning paradigms, reinforcement learning for a mobile robot, object tracking and motion estimation, 3D model construction, computer vision system and user modelling using dialogue strategies. This book will appeal to researchers, senior undergraduate/postgraduate students, application engineers and scientists.
Learning Visual Landmarks for Mobile Robot Topological Navigation -- Foveated Vision Sensor and Image Processing – A Review -- On-line Model Learning for Mobile Manipulations -- Continuous Reinforcement Learning Algorithm for Skills Learning in an Autonomous Mobile Robot -- Efficient Incorporation of Optical Flow into Visual Motion Estimation in Tracking -- 3-D Modeling of Real-World Objects Using Range and Intensity Images -- Perception for Human Motion Understanding -- Cognitive User Modeling Computed by a Proposed Dialogue Strategy Based on an Inductive Game Theory.
Keywords: Control engineering; Robotics; Mechatronics; Artificial intelligence; Control, Robotics, Mechatronics; Artificial Intelligence